GRAVE BACK PAIN: A CASE OF SOMASTOSTATIN RECEPTOR NEGATIVE METASTATIC PANCREATIC NEUROENDOCRINE NEOPLASM - N, Shamharini; S, Malarkodi; Ng, Danish OY; F, Siew Hui (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Somatostatin receptor (SSTR) status is an important prognostic marker ingastroenteropancreatic neuroendocrine neoplasms (NEN). Most NEN’s are SSTR-positive with only approximately 7.6% being receptor negative. Among these SSTR-negative neoplasms, 75% are in the pancreas. METHODOLOGY We describe a 60-year-old Malay male who presented with progressive lower back pain for six months, associated with constitutional symptoms and a palpable left supraclavicular lymph node. RESULTS Chest radiography revealed a mediastinal mass. Computed tomography (CT) scan showed metastatic disease with generalised lymphadenopathies, a subcutaneous right anterior chest wall nodule and multiple lesions in the lung, liver and tail of the pancreas. Magnetic resonance imaging revealed extensive spinal metastases. CT-guided core biopsy of the mediastinal lymph node was suggestive of NEN with a low proliferative index, Ki-67 (<5%). An endoscopic ultrasound-guided biopsy of the pancreatic lesion confirmed primary tumour. Clinical and biochemical assessment concluded the NEN to be non-functional. We proceeded with a Gallium-68 DOTATOC PET-CT scan, which showed absence of SSTR avid disease. A multidisciplinary meeting conceded the disease to be unresectable and chemotherapy with spinal radiation was concurred as definitive management. Systemic therapy options were limited by the SSTR-negative status, rendering him unsuitable for SSTR-dependant therapies. He deteriorated with a rapidly enlarging anterior chest wall mass. Unfortunately, he was unfit for chemotherapy due to recurrent infections and succumbed within two months of diagnosis. CONCLUSION In our patient, the low Ki-67 index reported from the biopsied specimen didn’t correlate with his rapid disease progression most probably due to intratumoural heterogeneity of Ki67 expression in NEN. SSTR-negative status carries a poor prognosis. It is associated with high grade tumours with limited treatment options. More research is required to explore the best therapeutic strategy in this uncommon setting. The overall prognosis is poor in view of the negative SSTR status, bulky metastases and unresectable primary.